2012
DOI: 10.1007/s00438-012-0673-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of the myelination genomic fabric

Abstract: This study aimed to quantify the influence of the astrocyte proximity on myelination genomic fabric (MYE) of oligodendrocytes, defined as the most interconnected and stably expressed gene web responsible for myelination. Such quantitation is important to evaluate whether astrocyte signaling may contribute to demyelination when impaired and remyelination when properly restored. For this, we compared changes in the gene expression profiles of immortalized precursor oligodendrocytes (Oli-neu), stimulated to diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 63 publications
(64 reference statements)
0
22
0
Order By: Relevance
“…Although the RNA was extracted from as homogeneous as possible tissue samples, the analysis provides the average expression levels for the variety of cells composing the myocardium: cardiomyocytes, fibroblasts, endothelial and smooth muscle cells, stem cell niches and supporting cells, nerve endings, immune system cells, etc. However, as we proved in previous publications [41,42], the transcriptome of each cell type is strongly modeled by the heterogeneous cellular environment, so that profiling each cell phenotype separately will give also a false picture. Therefore, we were particularly interested in genes expressed exclusively at cardiomyocyte level, such as those encoding different subunits of certain cardiac-specific voltage-dependent ion channels and transporters.…”
Section: Discussionmentioning
confidence: 83%
“…Although the RNA was extracted from as homogeneous as possible tissue samples, the analysis provides the average expression levels for the variety of cells composing the myocardium: cardiomyocytes, fibroblasts, endothelial and smooth muscle cells, stem cell niches and supporting cells, nerve endings, immune system cells, etc. However, as we proved in previous publications [41,42], the transcriptome of each cell type is strongly modeled by the heterogeneous cellular environment, so that profiling each cell phenotype separately will give also a false picture. Therefore, we were particularly interested in genes expressed exclusively at cardiomyocyte level, such as those encoding different subunits of certain cardiac-specific voltage-dependent ion channels and transporters.…”
Section: Discussionmentioning
confidence: 83%
“…In two previously published papers, we have shown that astrocyte-conditioned medium is a major regulator of gene expression in oligodendrocytes even in the absence of cytosol-to-cytosol communication via gap junction channels connecting these two cell types [29,30]. In the present study, we analyzed whether oligodendrocyte-conditioned medium changes significantly the astrocyte transcriptome.…”
Section: Discussionmentioning
confidence: 83%
“…This result is surprising because the oligodendrocytes responded to the presence of astrocytes by increasing the expression of Gjc2 (encoding Cx47), the Cx43 partner in heterocellular gap junction channels [74], by 9.70x. We determined the up-regulation of Gjc2 by re-analyzing the previously reported microarray data on Oli-neu with the same set up [29,30]. It should be noted that increased expression levels for gap junction proteins are not always matched with changes in coupling.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Fig. , pairwise relevant analysis revealed major alterations in the glutamatergic and GABAergic synapse genomic fabric topologies in betamethasone‐exposed animals, as well as the presence of substantial sex differences in controls and sex‐specific alterations in betamethasone‐exposed animals. In addition to the expression levels, this analysis also considers the contribution of expression controls and coordination of the paired genes with respect to the inter‐coordination and stability of the genomic fabric.…”
Section: Transcriptomic Analysis Of the Rat Model Of Infantile Spasmsmentioning
confidence: 86%
“…As a result of transcriptomic networks , by which expressions of individual genes are inter‐related, alteration of one key gene has ripple effects on many others [as observed in knockouts ( and knockdowns (. Moreover, transcriptomic networks may even cross cell boundaries mediated by intercellular signalling . Taken together, these findings indicate that intercellular communication integrates individual cells within multicellular structures so that transcriptomic events in one cell type modulate gene expression in others .…”
Section: Imprinting Effects Of Prenatal Corticosteroids On Gene Exprementioning
confidence: 97%